2010
DOI: 10.1002/humu.21142
|View full text |Cite
|
Sign up to set email alerts
|

A specific mutation in the distant sonic hedgehog (SHH)cis-regulator (ZRS) causes Werner mesomelic syndrome (WMS) while complete ZRS duplications underlie Haas type polysyndactyly and preaxial polydactyly (PPD) with or without triphalangeal thumb

Abstract: Werner mesomelic syndrome (WMS) is an autosomal dominant disorder with unknown molecular etiology characterized by hypo- or aplasia of the tibiae in addition to the preaxial polydactyly (PPD) of the hands and feet and/or five-fingered hand with absence of thumbs. We show that point mutations of a specific nucleotide within the sonic hedgehog (SHH) regulatory region (ZRS) cause WMS. In a previously unpublished WMS family, we identified the causative G>A transition at position 404 of the ZRS, and in six affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 28 publications
2
120
0
Order By: Relevance
“…Both entities are caused by mutations in the ZRS locus at chromosome 7q36 (LMBR1), encompassing a long-range regulator of SHH. 38,37 Syndactyly type V (Dowd type; fusion of 4/5 metacarpals) The hallmark of this type is the fusion of fourth and fifth metacarpals (Figure 2). Additional symptoms may involve shortening of fused fourth and fifth metacarpals, ulnar deviation of fingers from second to fifth, interdigital cleft between third and fourth fingers, camptodactyly of fifth finger, short distal phalanges, and absent distal interphalangeal creases of the affected fingers.…”
Section: Syndactyly Type I-d (Castilla Type; 4/5 Toes Syndactyly)mentioning
confidence: 99%
“…Both entities are caused by mutations in the ZRS locus at chromosome 7q36 (LMBR1), encompassing a long-range regulator of SHH. 38,37 Syndactyly type V (Dowd type; fusion of 4/5 metacarpals) The hallmark of this type is the fusion of fourth and fifth metacarpals (Figure 2). Additional symptoms may involve shortening of fused fourth and fifth metacarpals, ulnar deviation of fingers from second to fifth, interdigital cleft between third and fourth fingers, camptodactyly of fifth finger, short distal phalanges, and absent distal interphalangeal creases of the affected fingers.…”
Section: Syndactyly Type I-d (Castilla Type; 4/5 Toes Syndactyly)mentioning
confidence: 99%
“…The qPCR technique and the calculation method were described before. 6 The used TaqMan assay is based on amplification and quantification of IHH in relation to an internal reference gene, albumin (ALB), in a multiplex PCR using ABIPRISM7500 (Applied Biosystems, Foster City, CA, USA). The primers and probes for IHH (marked with FAM) and ALB (marked with VIC) were designed using the PRIMER EXPRESS software (Applied Biosystems) and were purchased from Applied Biosystems and Metabion (Martinsried, Germany) (for primer sequences see Supplementary Table 1).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…5 Although Ihh signaling has been correlated with digit growth, various forms of polydactyly have been mainly associated with altered expression of Sonic hedgehog (Shh). 6,7 It has been suggested that the interaction between Shh and Gli3 defines digit number and identity. 8 Conversely, the polydactylous phenotype of the mouse mutant doublefoot is caused by a deletion in cis to Ihh that leads to ectopic Ihh expression in the developing limb bud mesenchyme.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory mutations involving the ZRS activate Shh expression at an ectopic site along the anterior margin of the limb bud. [Lettice et al, 2003] This misexpression is central to a group of limb defects, which are called the "ZRS associated syndromes" [Wieczorek et al, 2010]. These defects include preaxial polydactyly type 2 and type 3 (PPD 2/3, MIM#s 174500, 174600), triphalangial thumb polysyndactyly (TPTPS; MIM# 190605)), syndactyly type IV (SD4; MIM# 186200), and Werner's mesomelic syndrome (MIM# 188770).…”
mentioning
confidence: 99%